The influence of polymorphic variants rs2305619 и rs3816527 of the PTX3 gene on clinical profile and outcomes in patients with hypertrophic cardiomyopathy: results of a 11-years follow-up - A. A. Streltsova; A. Ya. Gudkova; S. A. Pyko; E. N. Semernin; A. A. Kostareva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The objective of this study was to determine the association of polymorphic variants rs2305619 and rs3816527 of the PTX3 gene with clinical profile and outcomes in hypertrophic cardiomyopathy (HCM) patients.Methods and materials. The study population consisted of 153 patients ≥18 years old with a confirmed diagnosis of HCM. The control group included 200 healthy donors. Duration of follow-up was 11 years (2008–2019 yrs.). The study design included a new model for determining variants of the clinical profile and outcomes of HCM. Polymorphic variants rs2305619 and rs3816527 of the PTX3 gene were genotyped by polymerase chain reaction.Results. The mortality rate in patients ≥18 years old with 1, 2 and 3 adverse pathways of HCM progression was significantly higher, compared with those without adverse pathways (р<0.001). A combination of chronic heart failure (CHF) with midrange and reduced LVEF (<49 %) with 1, 2 and 3 adverse pathways in HCM patients occurred more frequently, compared with those who had CHF with preserved LVEF (≥50 %) (odds ratio (OR) = 0.168, 95 % confidence interval (CI) =0.068–0.412, р<0.001). The genetic testing showed no significant differences in genotype and allele frequencies of polymorphic variants rs2305619 and rs3816527 of the PTX3 gene in patients with HCM and control groups. It was found a tendency for increase in GG genotype frequency (p<0.068) and significant increase in G allele frequency of rs2305619 of the PTX3 gene in HCM patients ≥18 years old and CHF with mid-range and reduced LVEF (<49 %) (A:G, OR=0.521, 95 % CI=0.301–0.902, p<0.019). HCM patients (age – 63 [58; 75] years) and type 2 diabetes mellitus demonstrated high prevalence in AG and GG genotypes (p<0.008) and G allele frequencies of rs2305619 of the PTX3 gene (A:G, OR =1.952, 95 % CI=1.076–3.542, p<0.026).Conclusions. HCM progression along 1 and more adverse pathways in patients ≥18 years old has been characterized with adverse outcome. G allele of rs2305619 of the PTX3 gene is associated with CHF with mid-range and reduced LVEF (<49 %) in HCM patients ≥18 years old. The associations of G allele and AG and GG genotypes of rs2305619 of the PTX3 gene with diabetes type 2 are observed in elderly HCM patients.